Dictionary of scientific biography. [Volumes 13 & 14] - Gillispie, Charles Coulston; American Council of Learned Societies (New York : Charles Scribner's Sons, 1981)
Contains alphabetically arranged articles that provide information about the accomplishments and careers of scientists, from classical antiquity to modern times, who have made significant contributions either to their professions or the community of knowledge; covering the fields of math, astronomy, physics, chemistry, biology, and the earth sciences. Arranged alphabetically from Staudinger to Zwelfer.
v. 13. Herman Staudinger-Giuseppe Veronese -- v. 14. Addison Emery Verrill-Johann Zwelfer.
"Published under the auspices of the American Council of Learned Societies"--P. facing t.p.
Includes bibliographical references.
Wilson's Senior High School.
Young Adult
Keywords: Scientists -- Biography -- Dictionaries; Scientists -- Biography -- Dictionaries